Cerebral venous thrombosis in otorhinolaryngology. Case report - Aleksandr A. Krivopalov; Aleksandr Yu. Shcherbuk; Yurii A. Shcherbuk; Irina I. Sarkisyan; Polina A. Shamkina; Alexandra I. Glyshchenko (ZAO "Consilium Medicum", 2022)
A violation of cerebral circulation, in which a blood clot forms in the venous system of the brain with the formation of an obstruction of the dural sinus, one or more veins of the brain is called cerebral venous thrombosis. Cerebral venous sinus thrombosis (CVT) is a rare venous thromboembolic event, which accounts for 5 cases per 1 million among adults and about 7 cases per 1 million among children, according to the International Study on Cerebral Vein and Dural Sinus Thrombosis. Women of childbearing age are more susceptible to the disease, which is probably due to hormonal changes during pregnancy, labor, as well as the concomitant effect of oral contraceptives (leading to hypercoagulation). In addition to the low prevalence of CVT, the variety of etiology, the diagnosis is complicated by the highly variable clinical picture of cerebral venous thrombosis. The clinical manifestations of CVT are very diverse and depend on the prevalence of thrombosis, the rate of formation of vein occlusion, the age of patients, and the etiological factor. The main symptom of CVT is an intense headache (92%) as a sign of developing intracranial hypertension. During more than 2 years of follow-up, the mortality rate from CVT was calculated 8.3%, however, in more than 90% of cases the prognosis of the disease is favorable. Despite the favorable prognosis, without timely treatment of CVT, this is a potentially lethal disease, so the relevance of this topic is beyond doubt.